1987
DOI: 10.1111/j.1399-6576.1987.tb02571.x
|View full text |Cite
|
Sign up to set email alerts
|

Change in tracheal blood flow during endotracheal intubation

Abstract: Changes in blood flow in the tracheal mucosa of the dog caused by the pressure exerted by high volume, low-pressure cuffs were measured with the hydrogen clearance method. Before inflating the cuffs, the blood flow of the tracheal mucosa was measured as a control for 12 h in order to confirm that the procedures of the hydrogen clearance method itself had little or no influence on the blood flow in the tracheal mucosa. After inflating the cuffs to create a tracheal wall pressure (TWP) of 1.3 kPa (10 mmHg), 2.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
3

Year Published

1994
1994
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 9 publications
2
26
0
3
Order By: Relevance
“…10 Of course, the LMA-ProSeal exerts pressure on the pharyngeal structures similar to other inflatable airway devices. 11,12 Several studies have reported the association of using an LMA-ProSeal with injuries to the lingual and recurrent laryngeal nerves. 13,14 The four cases of perilaryngeal leakage during pneumoperitoneum in the LMA-ProSeal group could be explained by displacement of the LMAProSeal caused by diffusion of N 2 O into the cuff.…”
Section: Discussionmentioning
confidence: 99%
“…10 Of course, the LMA-ProSeal exerts pressure on the pharyngeal structures similar to other inflatable airway devices. 11,12 Several studies have reported the association of using an LMA-ProSeal with injuries to the lingual and recurrent laryngeal nerves. 13,14 The four cases of perilaryngeal leakage during pneumoperitoneum in the LMA-ProSeal group could be explained by displacement of the LMAProSeal caused by diffusion of N 2 O into the cuff.…”
Section: Discussionmentioning
confidence: 99%
“…The tracheal tube (TO cuff expands within the rigid confines of the tracheal rings and it has been shown that a large reduction in tracheal blood flow occurs at cuff pressures >20 mmHg, 7 A pressure in a tracheal cuff >50 mmHg for only 15 min can destroy columnar epithelium and will partially denude the basement membrane. 8 The relationship between mucosal pressure and LMA cuff pressure is more complex. Unlike the trachea, the pharynx is a highly distensible structure which is normally subject to large transient pressure changes and distortion under many physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Pesquisas clínicas têm demonstrado diversos tipos de lesões de mucosa laríngea e traqueal após a intubação por períodos variáveis de tempo, sendo este um dos fatores determinantes do agravamento das lesões 9,10 . Devido à configuração da glote em "V", as principais lesões ocorrem na porção posterior da laringe, no nível dos processos vocais, onde a sonda encontra-se em íntimo contato com a mucosa.…”
Section: Lesões Secundárias Ao Contato Da Cânula Ou De Seu Balonete Sunclassified